The radical Isaac : I.L. Peretz and the rise of Jewish socialism - Mahalel, Adi (Albany : State University of New York Press, 2023)
Examines the Yiddish-Hebrew writer I. L. Peretz's alignment with the Jewish working-class in Eastern Europe and his devotion to progressive politics.
Front Matter -- Contents -- Illustrations -- Acknowledgments -- Intellectual and Historical Backdrop of Peretz's Early Work, Outline, and Methodology -- Education, Professions, and Literary Proclamations -- A Radical Shift -- "To Be a Fighter with Both Fists!" -- Peretz's 1890s Hebrew and Yiddish Poetry -- Between Liberal Satire and Socialist Roots -- Conclusion -- Appendixes -- Notes -- Index
Includes bibliographical references and index.
Online resource; title from PDF title page (ProQuest Ebook Central platform, viewed June 5, 2023).
JSTOR
Keywords: Peretz, Isaac Leib, -- 1851 or 1852-1915 -- Criticism and interpretation; Peretz, Isaac Leib, -- 1851 or 1852-1915 -- Political and social views; Peretz, Isaac Leib, -- 1851 or 1852-1915; BIOGRAPHY & AUTOBIOGRAPHY / Jewish; Political and social views; Literary criticism; Criticism, interpretation, etc; Literary criticism; Critiques littéraires.